Boys and Girls in the Classroom—About Didactical Perspectives in Similarities and Differences - Ingela Stenberg; Lena Boström (Education Sciences)
The lower academic performance of boys in compulsory school has long been a well-known fact, but only in the last decade has it been shown in the public debate. Various explanations for boys’ underperformance mainly include background, expectations, norms, and hierarchical gender order. Few studies have focused on what can be affected, namely the teaching in the classroom. In addition, studies have not, to any significant extent, focused on the students’ perceptions. This study was conducted through eight group interviews with 2nd and 5th-grade students and explored how boys and girls perceive learning in a classroom context. Similarities and differences in perceptions emerged through a reflexive thematic analysis from a didactic theoretical perspective—the similarities in perception concerned the teacher’s leadership, interactions, learning strategies, and learning environment. The differences were about reprimands, different developed learning strategies, confidence in the teacher, and the social atmosphere. The result indicates a need for the teacher to be more aware of the processes going on in the classroom and to build both social and learning support structures with a focus on learning strategies.